Fifty-five-year longevity for the largest member of the family Sparidae: the endemic red steenbras Petrus rupestris from South Africa. Issue 4 (2nd October 2018) - Andrews, AH; Smale, MJ; Cowley, PD; Chang, N
Abstract : A previous study that explored the age and growth of red steenbras Petrus rupestris (Valenciennes, 1830), a large sparid (family Sparidae, seabreams or porgies) endemic to South Africa and reported to approach 2 m in length, provided estimates as a moderately slow-growing species with a maximum age near 30 years. The stock is considered collapsed and a fishing moratorium was imposed in 2012, resulting in this species being assessed as Endangered by the IUCN. One consideration in addressing population status is validation of life-history traits. In this study, estimates of age for red steenbras from thin-sectioned otoliths were reassessed visually in terms of both the original ages and revised estimates using a different age-reading pattern. The revised ages exceeded the original ages by up to 30 years, with a maximum estimated age of 55 years from a well-defined otolith section that provided a basis for the revised age-reading procedure. Bomb radiocarbon ( 14 C) dating revealed there was an offset in the timing of the 14 C rise on the Agulhas Bank that, when coupled with considerations for regional oceanography, provided support for the revised age-reading pattern and an estimated longevity that exceeds 50 years. These findings were further supported by the fortuitous recapture of a tagged red steenbras that was at liberty for 22 years.